Porous graphene nanosheets functionalized thin film nanocomposite membrane prepared by interfacial polymerization for CO2/N2separation - Li, H.; Ding, X.; Zhang, Y.; Liu, Jian (Elsevier BV, 2017)
© 2017 Elsevier B.V. The inherent defects of porous graphene (PG) formed during reduction etching process could serve as nanopores, making PG emerge a potential application for the preparation of micrometre-sized separation membranes. Here, we introduced PG as inorganic nanofiller to fabricate thin film nanocomposite (TFN) membranes for CO2capture via interfacial polymerization technique. The PG selective nanolayers not only possessed a good adhesion with polymers but also benefited from hydrogen bonding actions, simultaneously, thus ensuring the formation of high-efficiency molecular sieving passageway in the separation layer of membranes. Furthermore, the thin PG nanosheets were verified to have an significantly affect for permeability and selectivity of membranes (PG, 0.05 wt%, 1 bar), with exhibiting about 21% and 20.8% enhancement of the CO2permeance and the CO2/N2selectively compared to that of the membrane without PG separately. Simultaneously, the membrane also showed higher stability and the porous surface morphology of PG shortened greatly the gas transfer path. The approach offers a potential promising to exploit the ultra-thin film composite membrane for efficient gas separation.